1996
DOI: 10.1128/iai.64.1.1-9.1996
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of immune responses of mice immunized with five different Mycobacterium bovis BCG vaccine strains

Abstract: Among the various parameters which may contribute to Mycobacterium bovis BCG vaccination efficiency, the choice of the vaccine strain may play an important role. In the present study, we therefore compared the immunogenicity of five different BCG strains that are commonly used for BCG vaccine production (Glaxo 1077, Japanese 172, Pasteur 1173P2, Prague, and Russian strains). The comparison of the growth capacity of these BCG strains in BALB/c and C3H mice demonstrated that a great difference exists between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
45
1
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 148 publications
(54 citation statements)
references
References 34 publications
7
45
1
1
Order By: Relevance
“…Few CFU were found in oropharyngeal and intestinal mucosa: less than 50 to 900 CFU per organ. This is in accordance with previous findings (28). The largest number of viable rBCG was found in feces (more than 10 6 CFU per g).…”
Section: Recovery Of Rbcg In Gastrointestinal Lymphoid Tissues and Tasupporting
confidence: 93%
“…Few CFU were found in oropharyngeal and intestinal mucosa: less than 50 to 900 CFU per organ. This is in accordance with previous findings (28). The largest number of viable rBCG was found in feces (more than 10 6 CFU per g).…”
Section: Recovery Of Rbcg In Gastrointestinal Lymphoid Tissues and Tasupporting
confidence: 93%
“…Furthermore, the proliferative T-cell response to BCG has been shown to be strain-dependent. Lagranderie et al found that vaccination of BALB/c mice both with the Pasteur 1173P2 strain and a Russian strain induced a significant proliferative response, including production of IFN-g to PPD in mesenteric lymph node cells, whilst a similar response to other strains was absent [34]. In our study, using native BCG, we found IFN-g secretion in splenic cells indicative of a proliferative systemic T-cell response to this strain.…”
Section: Discussionsupporting
confidence: 59%
“…The precautions taken since the 1960s to avoid mutation are likely to have kept the strains almost unchanged. Before this date, the conservation techniques allowed some variation in the BCG strains from one country to another (9,12). Analysis of the genomes of the different BCG daughter strains by pulsed-field gel electrophoresis showed major differences (22).…”
Section: Resultsmentioning
confidence: 99%